Effect of CaCO3 whiskers on tensile properties of ultra-high-performance engineered cementitious composites. (1st October 2022) - Wu, Li-Shan; Yu, Zhi-Hui; Zhang, Cong; Bangi, Toshiyuki
Abstract: Ultra-high-performance engineered cementitious composite (UHP-ECC) is expected to become an ideal construction material for its superior mechanical properties. However, the high cost of UHP-ECC, especially the use of expensive synthetic fibers, limiting its extensive engineering application. To address this, cheap calcium carbonate (CaCO3 ) whiskers were utilized to partially replace polyethylene (PE) fibers. The various volume fractions of PE fibers and CaCO3 whiskers were adapted to possess different tensile properties (ultimate tensile stress, strain capacity, crack number, and strain energy). The results indicated that the decrease in PE fiber content from 2% to 1.5% significantly deteriorated tensile properties of UHP-ECC (the decrease of 24.95% in tensile strength and 49.47% in strain capacity). However, the partial replacement of PE fibers by CaCO3 whiskers could effectively mitigate the performance degradation and improve the stable multiple cracking behavior. Especially, the tensile ductility of UHP-ECC with a combination of 1.75% PE fibers and 0.5% CaCO3 whiskers was 45.19% higher than that of UHP-ECC with mono 1.75% PE fibers, and also 102.5% higher than that of control group (2% PE fibers). Scanning electron microscopy images confirmed the synergistic effect of PE fibers and CaCO3 whiskers at the microscopic level. In according with micromechanics, the addition of CaCO3 whiskers could effectively improve the complementary energy of UHP-ECC by micro cracking arresting, which increased the pseudo strain hardening values and thus leading to the enhancement in tensile ductility of UHP-ECC. In addition, the hybrid fiber reinforcing index ( RI v ) had a positive correlation with the tensile properties of UHP-ECC. Therefore, a semi-empirical formula based on RI v could be adopted for the property prediction of UHP-ECC with different combination of PE fibers and CaCO3 whiskers. Highlights: The reduction in PE fibers content led to the deterioration of tensile properties due to the dominant effect of PE fibers in UHP-ECC. The partial replacement of PE fibers by cheap CaCO3 whiskers could effectively improve the tensile ductility, multiple cracking behavior of UHP-ECC. A semi-empirical formula was utilized to predict the tensile properties of UHP-ECC with different combinations of PE fibers and CaCO3 whiskers.